Pengaruh Profitabilitas, Likuiditas, Earning Per Share, dan Penghindaran Pajak Terhadap Harga Saham pada Perusahaan Indeks LQ45 yang Terdaftar di Bursa Efek Indonesia Periode 2018 -2021 - Fitri Handayani; Susanti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The objective of the research was to find out the influence of Profitability, Liquidity, Earning per Share (EPS), and Tax Avoidance on Stock Price in the LQ45 Index companies listed in BEI (Indonesian Stock Exchange) Period 2018 - 2021. The research used associative causal method. The samples were 23 LQ45 companies listed in BEI (Indonesian Stock Exchange) in the period 2018 – 2021, taken by using purposive sampling technique. Secondary data were analyzed by using multiple linear regression analysis and interaction (moderating) test with SPSS 25 software program. The result of the research showed that, partially, Earnings per Share (EPS) had positive and significant influence on stock prices while Profitability, Liquidity, and Tax Avoidance have no insignificant influence on stock prices.